Olbia, Ukraine: Grautonige Keramik der ersten Jahrhunderte n. Chr. im Unteren Bug-Gebiet - Schultze, Erdmute (e-Forschungsberichte des DAI, 2023)
The main focus of the research project is to clarify the relation between the antique centre of Olbia and its vicinity with regards to the pottery production as a part of the economic structure. The grey wheel-made ceramics from all sites could be divided into two separate spectra of vessels of different shapes and decorations – Greek-Roman and Chernyakhov pottery. In 2013 portable XRF analysis was implemented for 284 samples from the area in study. As a result different pottery-groups could be identified by comparing their different chemical elements. Furthermore some preliminary results were obtained by comparing two spectra of vessels and four groups based on P-XRFAnalysis.